Effects of HIF-1α and HIF2α on Growth and Metabolism of Clear-Cell Renal Cell Carcinoma 786-0 Xenografts. (27th May 2010) - Biswas, Swethajit; Troy, Helen; Leek, Russell; Chung, Yuen-Li; Li, Ji-liang; Raval, Raju R.; Turley, Helen; Gatter, Kevin; Pezzella, Francesco; Griffiths, John R.; Stubbs, Marion; Harris, Adrian L.
Abstract : In cultured clear-cell renal carcinoma (CCRCC) 786-0 cells transfected with HIF1α (HIF-1+), HIF-2α (HIF-2+), or empty vector (EV), no significant differences were observed in the growth rates in vitro, but when grown in vivo as xenografts HIF-2α significantly increased, and HIF-1α significantly decreased growth rates, compared to EV tumors. Factors associated with proliferation were increased and factors associated with cell death were decreased in HIF-2+ tumors. Metabolite profiles showed higher glucose and lower lactate and alanine levels in the HIF-2+ tumors whilst immunostaining demonstrated higher pyruvate dehydrogenase and lower pyruvate dehydrogenase kinase 1, compared to control tumors. Taken together, these results suggest that overexpression of HIF-2α in CCRCC 786-0 tumors regulated growth both by maintaining a low level of glycolysis and by allowing more mitochondrial metabolism and tolerance to ROS induced DNA damage. The growth profiles observed may be mediated by adaptive changes to a more oxidative phenotype.